Morel-Lavallée Lesion in Sports. Issue 6 (November 2016) - Khodaee, Morteza; Deu, Rajwinder S.; Mathern, Seth; Bravman, Jonathan T.
Abstract : Posttraumatic soft tissue swelling is a relatively common presenting complaint among athletes. Due to its broad differential diagnosis, a comprehensive evaluation beginning with history and physical examination are recommended. Imaging including radiography, ultrasound, and magnetic resonance imaging (MRI) are preferred modalities. Aspiration of a fluid collection, preferably under ultrasound guidance, may help with the diagnosis and management of some of these conditions. Morel-Lavallée lesion (MLL) is an uncommon condition consisting of a closed degloving injury caused by forces that create pressure and shear stress between the subcutaneous tissue and the superficial fascia or bone. Most commonly, MLL is found over the greater trochanter and sacrum, but in rare cases can be found in other regions of the body. In most cases, concurrent severe injury mechanisms are present. Sports-related MLL are rare and underreported. Depending on the stage and type of MLL, therapeutic strategies may vary from compression wraps and aspiration to surgical evacuation.